Regulation of the Host Antiviral State by Intercellular Communications - Assil, Sonia (Viruses, 2015)
Viruses usually induce a profound remodeling of host cells, including the usurpation of host machinery to support their replication and production of virions to invade new cells. Nonetheless, recognition of viruses by the host often triggers innate immune signaling, preventing viral spread and modulating the function of immune cells. It conventionally occurs through production of antiviral factors and cytokines by infected cells. Virtually all viruses have evolved mechanisms to blunt such responses. Importantly, it is becoming increasingly recognized that infected cells also transmit signals to regulate innate immunity in uninfected neighboring cells. These alternative pathways are notably mediated by vesicular secretion of various virus- and host-derived products (miRNAs, RNAs, and proteins) and non-infectious viral particles. In this review, we focus on these newly-described modes of cell-to-cell communications and their impact on neighboring cell functions. The reception of these signals can have anti- and pro-viral impacts, as well as more complex effects in the host such as oncogenesis and inflammation. Therefore, these “broadcasting” functions, which might be tuned by an arms race involving selective evolution driven by either the host or the virus, constitute novel and original regulations of viral infection, either highly localized or systemic.